Kulidawa, Emas Hijau Yang Tergusur - La Ode Topo Jers (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
This study was taken place in Muna, Southeast Sulawesi, which is famous for its teak forests. Ethnographic method is used to assess the reality of life associated with forest destruction. There appeared to recriminations between the government and the society about the actors of forest destruction. Starting from forest management policies that are not obvious by the government, deforestation happened, people started to cut trees without replanting. Since it is considered as vacant land, people claim it as customary land for the benefit of their lives. Keywords: teak forest, forest management, deforestation, policies